(untitled) (Ustozlar uchun, 2025)
. This article examines the comparative effectiveness of traditional and online education in teaching English as a Foreign Language (EFL). It analyzes how each method influences learners’ motivation, language proficiency, and communication skills. The paper highlights the strengths and weaknesses of both approaches, showing that traditional education enhances social interaction and immediate feedback, while online learning offers flexibility and access to diverse resources. The study concludes that a blended learning model combining both methods provides the most effective results for English language acquisition.